Condição da mulher e educação feminina no Jornal O Operário (1909-1913): aproximações e distanciamentos entre positivismo e anarquismo - Pereira, Keyla Priscilla Rosado (2019)
This dissertation has as theme the issue of female education at the First Republic, in Sorocaba/SP, based on the publications present in the newspaper O Operário (1909-1913), especially those that were signed by women. The problem that oriented this investigation questioned the different biases presents in this publications made by them. For this purpose, the qualitative and documental-bibliographical types of research were used, and the facsimile version of the newspaper was consulted. O Operário was a bi-weekly newspaper aimed at the working class to give them "a voice". Open to diverse participation, it counted with publications of men and women, some of them dealing with the issues of education and being based on distinct ethical-political paradigms. In a Sorocaba that, on the one hand, had an elite excited by the modernization of the "Manchester Paulista" and, on the other hand, with an working class formed mostly by immigrants, subject to the most diverse adversities, O Operário covered voices that looked at education, both by the rational-scientific (positivist) bias and by the rational-libertarian (anarchist) bias. Therefore, the aim of the research was to analyze the approximations and distances between these two paradigms, based on the publications present in the newspaper that concern the issue of female education.